Investigation of a nosocomial outbreak by alginate-producing pan-antibiotic-resistant Pseudomonas aeruginosa - Yakupogullari, Yusuf; Otlu, Baris; Dogukan, Muruvvet; Gursoy, Canan; Korkmaz, Ebru; Kizirgil, Ahmet; Durmaz, Riza (Mosby-Elsevier, 2008)
Background: The nosocomial spread of pan-antibiotic-resistant nonfermentative bacteria is an increasing concern. This study investigated the microbiologic and epidemiologic characteristics of a hospital outbreak due to alginate-producing, pan-antibiotic-resistant Pseudomonas aeruginosa (PAR-Pa). Methods: All patients with infection with a P aeruginosa strain that was resistant to all Clinic Laboratory Standards Institute-suggested antimicrobial agents between November 2004 and May 2005 were included in the study. Alginate production detection and pulsed-field gel electrophoresis (PFGE) typing were done for the patient and environmental surveillance isolates. A matched case-control study was performed to identify risk factors and evaluate outcomes. Results: PFGE analysis of a total of 35 PAR-Pa isolates (28 patient and 7 environmental surveillance isolates) identified a single epidemic clone as responsible for the outbreak. All epidemic isolates were alginate-producing and susceptible only to colistin. The Student t-test demonstrated that a longer stay in the intensive care unit (ICU) (6.64 days vs 1.83 days; P < .05) significantly increased the risk of PAR-Pa infection. Systemic PAR-Pa infection resulted in higher mortality (85.7% vs 27.8%; P < .05). Multivariate analysis determined that therapeutic failure (odds ratio 5 24.7; 95% confidence interval 5 4.144 to 147.221; P < .05) was the independent risk factor related to this high mortality. Localized PAR-Pa infections were associated with longer hospital stays (46.2% vs 14.4%; P < .05) and higher rates of surgery (85.7% vs 15.4%; P < .05) and amputation (42.8% vs 0%; P < .05). The recovery of the pathogen from staff hands and frequently handled surfaces suggests possible handborne transmission. Improved hygienic standards and application of strict contact precautions, including isolation, reduced the spread of the pathogen. Conclusion: This study illustrates the ability of pan-antibiotic-resistant P aeruginosa to cause an outbreak with significant mortality and stresses the need for precautions to prevent the spread of such highly resistant strains.
Keywords: Infections; Colistin